The temperature dependence of greenhouse gas production from Central African savannah soils - Girkin, Nicholas T.; Cooper, Hannah V.; Johnston, Alice S. A.; Ledger, Martha; Niamba, G. R. Mouanda; Vane, Christopher H.; Moss-Hayes, Vicky; Crabtree, Dafydd; Dargie, Greta C.; Vasquez, Saul; Bocko, Yannick; Mampouya Wenina, Emmanuel; et al. (Elsevier, 2025)
Savannahs cover 20 % of the global land surface, but there have been few studies of greenhouse gas (GHG) dynamics from savannah soils. Here, we assess potential turnover of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) from surface (0–10 cm) and subsurface (20–30 cm) soils from two contrasting tropical savannah sites in the Republic of Congo, Central Africa, under dry (40 % water-filled-pore-space, WFPS) and wet (70 % WFPS) conditions. Under baseline conditions (25 °C), we found soils were sources of CO2 and N2O, but a sink for CH4. Assessment of the temperature response of GHG fluxes between 20 and 35 °C revealed variable temperature dependences. That is, CO2 fluxes showed a strong temperature response, whereas the temperature response of N2O fluxes was only significant under dry conditions, and no significant temperature response of CH4 fluxes was observed. The temperature quotient (Q10) of soil respiration increased from 1.58 ± 0.004 to 1.92 ± 0.006 at sites with lower soil organic carbon contents. The relative increase in N2O with CO2 fluxes across temperatures was significantly influenced by moisture conditions at both sites. No temperature or soil moisture response was observed for CH4 fluxes, collectively implying divergent GHG responses to changing climatic conditions. Using Rock-Eval pyrolysis we assessed the organic chemistry of all soil types, which indicated contrasting degrees of stability of carbon sources between sites and with depth which, alongside significant differences in a range of other soil parameters (including organic matter content, total carbon, total nitrogen, electrical conductivity, and pH), may account for site-specific differences in baseline GHG emissions. Taken together, our results are amongst the first measures of GHG temperature sensitivity of tropical savannah soils, and demonstrate that soil CO2 emissions are more sensitive to warming and changes in moisture than the emissions of other GHGs, although relatively low compared to responses reported for soils from other tropical ecosystems. This implies that GHG fluxes form savannah soils in the region may be at least partially resilient to climate-induced soil warming compared to other ecosystems.
Keywords: Carbon dioxide; Methane; Nitrous oxide; Temperature sensitivity; Savannah; Tropical soil; Q10; 4101 Climate Change Impacts and Adaptation; 41 Environmental Sciences; 4106 Soil sciences